2022
DOI: 10.3847/1538-4357/ac6bf4
|View full text |Cite
|
Sign up to set email alerts
|

SNR G292.0+1.8: A Remnant of a Low-mass-progenitor Stripped-envelope Supernova

Abstract: We present a study of the Galactic supernova remnant (SNR) G292.0+1.8, a classic example of a core-collapse SNR that contains oxygen-rich ejecta, circumstellar material, a rapidly moving pulsar, and a pulsar wind nebula (PWN). We use hydrodynamic simulations of the remnant’s evolution to show that the SNR reverse shock is interacting with the PWN and has most likely shocked the majority of the supernova ejecta. In our models, such a scenario requires a total ejecta mass of ≲3 M ⊙ and implies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…Recent simulations show that inhomogenous surrounding environments are reflected in the forward and reverse shock for only ≈2000 yr (Orlando et al 2022). There is also evidence that G292ʼs morphology is influenced by the motion of its surviving pulsar (Temim et al 2022).…”
Section: Comparison To Other O-rich Snrsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent simulations show that inhomogenous surrounding environments are reflected in the forward and reverse shock for only ≈2000 yr (Orlando et al 2022). There is also evidence that G292ʼs morphology is influenced by the motion of its surviving pulsar (Temim et al 2022).…”
Section: Comparison To Other O-rich Snrsmentioning
confidence: 99%
“…They offer unique opportunities to probe the elemental distribution of metal-rich ejecta and investigate the progenitor star's mass-loss history at fine scales (see Lopez & Fesen 2018 for a review). Young, nearby oxygen-rich (O-rich) SNRs, created from the collapse of massive stars (zero-age main sequence, ZAMS, mass > 8 M e ; Smartt 2009), are especially informative to study core-collapse dynamics because they are often associated with progenitor stars that were largely stripped of their hydrogen envelopes (e.g., Blair et al 2000;Chevalier 2005;Temim et al 2022). The kinematic and chemical properties of their metal-rich ejecta retain information about the parent supernova explosion that would otherwise be lost in an H-rich explosion (Milisavljevic et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…They are physically interesting and important probes of both the explosion and nature of progenitor stars (see, e.g., the reviews of Vink 2012 andDubner &Giacani 2015). For example, estimates of ejecta masses, velocities, and energies constrain the progenitor and explosions (e.g., Temim et al 2022;Braun et al 2023). They are laboratories for shock physics (e.g., Raymond et al 2020aRaymond et al , 2020b.…”
Section: Introductionmentioning
confidence: 99%
“…Supernova remnants (SNRs) that show optical emission from supernova (SN) ejecta and circumstellar medium (CSM) are rare, but they provide unique information about the SN progenitor and about the explosion. There are a handful of oxygen-rich SNRs in the Galaxy and the Magellanic Clouds such as Cas A, G292.0+1.8, N132D, and 1E102-72.3 (Blair et al 2000;Hwang & Laming 2012;Temim et al 2022), but only three oxygen-rich SNRs are known in other galaxies (NGC 4449 and M83;Blair et al 1984;Lee & Lee 2014;Winkler et al 2017), and it is somewhat surprising that so few SNRs like Cas A have been found in surveys of other galaxies. Nitrogen-rich SNRs are even more rare.…”
Section: Introductionmentioning
confidence: 99%